Is it still important to be light in ski jumping? - Virmavirta, M.; Kivekäs, J. (Sports Biomechanics, 2021)
In ski jumping low body weight development resulted in some serious underweight problems and therefore the International Ski Federation (FIS) decided to solve the problem by relating maximum ski length to Body Mass Index (BMI) in 2004. The present study examined the current relationship between body weight, ski length and performance (jumping distance) in ski jumping. By adopting the BMI regulation to specifications for competition equipment, the FIS succeeded in stopping the alarming development of underweight problems in ski jumping. However, as the results of the present study show, the BMI regulation adopted by the FIS has reduced the advantage of being light, but despite the use of shorter skis it is still beneficial to be light within certain limits. The present parametric study suggests that the weight of the jumper is a more sensitive factor to jump length than ski area (ski length). In fact, sensitivity analysis shows that reducing BMI by 1% requires a reduction of approximately 2.0% in ski area to compensate each other. Based on the available information of the complex relationship between body morphology and performance in ski jumping there seems to be no further need for a change in the BMI regulation.